2016
DOI: 10.5194/gmd-9-2533-2016
|View full text |Cite
|
Sign up to set email alerts
|

Numerical framework and performance of the new multiple-phase cloud microphysics scheme in RegCM4.5: precipitation, cloud microphysics, and cloud radiative effects

Abstract: Abstract. We implement and evaluate a new parameterization scheme for stratiform cloud microphysics and precipitation within regional climate model RegCM4. This new parameterization is based on a multiple-phase one-moment cloud microphysics scheme built upon the implicit numerical framework recently developed and implemented in the ECMWF operational forecasting model. The parameterization solves five prognostic equations for water vapour, cloud liquid water, rain, cloud ice, and snow mixing ratios. Compared to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 58 publications
0
37
0
Order By: Relevance
“…Aerosols in RIEMS-Chem include sulfate, nitrate, ammonium, BC, OC, SOA, five bins of soil dust and five bins of sea salt (Han et al, 2012;Li and Han, 2016). ISORROPIA (Nenes et al, 1998) was coupled to RIEMS-Chem to treat thermodynamic equilibrium process and to simulate inorganic aerosols. SOA production from primary anthropogenic and biogenic VOCs is calculated using a bulk aerosol yield method according to Lack et al (2004).…”
Section: Cu Physicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aerosols in RIEMS-Chem include sulfate, nitrate, ammonium, BC, OC, SOA, five bins of soil dust and five bins of sea salt (Han et al, 2012;Li and Han, 2016). ISORROPIA (Nenes et al, 1998) was coupled to RIEMS-Chem to treat thermodynamic equilibrium process and to simulate inorganic aerosols. SOA production from primary anthropogenic and biogenic VOCs is calculated using a bulk aerosol yield method according to Lack et al (2004).…”
Section: Cu Physicsmentioning
confidence: 99%
“…In the atmosphere, SOA is mainly formed from the condensation of semi-volatile VOCs, which are the products of the oxidation of primary VOCs. An em-pirical two-product model (Odum et al, 1996) is often used to simulate SOA formation, but this method was reported to significantly underestimate measured SOA mass concentrations (Heald et al, 2008). Later, the volatility basis-set (VBS) approach (Donahue et al, 2006) was developed to represent the wide range of the volatility of organic compounds and complex processes.…”
Section: Pm 25 and Pm 25 Chemical Composition Distributionmentioning
confidence: 99%
“…However, due to the computational level, the complexity of cloud microphysical processes and the complex relationship between cumulus scale and large‐scale circulation, many CCSs are still summarized from experience (Arakawa, ). Convective clouds are represented by cumulus parameterizations, which mostly focus on dynamical and thermodynamical processes and treat the cloud microphysics in simplified ways (Nogherotto et al ., ). The characteristics of the CCSs are under certain closed assumptions, and the convection triggering function is defined through some assumptions.…”
Section: Conclusion and Discussionmentioning
confidence: 97%
“…Nogherotto et al . () and Yang et al . (; ) have both provided a more detailed introduction to RegCM4.5.…”
Section: Model and Datamentioning
confidence: 91%
See 1 more Smart Citation